Description of a new species of Hippopsis Lepeletier & Audinet-Serville and comments on the identity of H. quadrivittata Breuning (Coleoptera, Cerambycidae, Lamiinae, Agapanthiini) - Josef Vlasak; Antonio Santos-Silva (Papéis Avulsos de Zoologia, 2023)
Abstract Hippopsis sexlineata, a new species from Ecuador is described. The identity of Hippopsis quadrivittata Breuning, 1940 sensu auctorum is discussed and considered to be Hippopsis fractilineaBates, 1866.